Evaluation of the economic efficacy of vaccination against pertussis based on real-world data - S. V. Svetlichnaya; L. A. Elagina; L. D. Popovich (Реальная клиническая практика: данные и доказательства)
Mass vaccination against pertussis in our country has decreased the frequency of this infection. The lack of the total vaccination in children in 80-90 yy XX c led to the growth of morbidity in the current moment. Return in active vaccination / revaccination of population against pertussis is a demand of the time. Economic aspects of this kind approach to the social health care are required for an evaluation based on RWD.Materials and methods: Calculation of the macroeconomic effects of vaccination against pertussis has been performed with Far East Federal Region (FEFR) example for buster in children 6-7 y. o. based on RWD and prognosis of morbidity annually. A unique model of the epidemiology of pertussis in FEFR has been created with RWD statistics and the Global burden of diseases project usage. The size of the virtual cohort of children 6-7 y. o. was established as 100 thousand. It has been assumed that 95 % from this cohort will receive buster of the tetanus toxoid, reduced diphtheria toxoid and acellular pertussis vaccine, combined, adsorbed (INN) with its efficacy and cost consideration. The monetary equivalent of the epidemiologic benefit due to disease prevention in the vaccinated children with regional GDP per capita has been calculated.Results: The total summarized benefit due to illness prevention after buster in children in FEFR could be as 21,15 mln RUR annually, and due to mortality reduction in the life years expectation horizon — of 50,45 mln RUR. The total economic profit of the buster revaccination against pertussis in children 6-7 y. o. with its influence on morbidity in children of younger age groups can lead to 198,69 bln RUR during the 7-year horizon of vaccine efficacy.Conclusion: RWD is a base for modeling and potential prognosis of epidemiological process and results of this job are proved the economic necessity for buster vaccination against pertussis in children 6-7 y. o. in the Russian Federation.